Movimiento de remoción de masa y reducción del riesgo en el barrio Tambán, cantón Chimbo, provincia de Bolívar, año 2021 - Blacio Ochoa, Tatiana Elizabeth (2022)
The objective of this study is to reduce the risk in the Tambán neighborhood caused by the existing landslides in the Chimbo canton, province of Bolívar, considering the importance of safeguarding the integrity of the people and being able to reduce as much as possible the risk that the inhabitants of the sector face on a daily basis. Bearing in mind that the landslide already occurred in December, we were able to directly observe the management of the event, sampling and response, allowing us to establish a diagnosis of the current situation of the sector. In addition, to recognize the impact of the vulnerability developed at the physical, economic, environmental and social levels, so that once the areas with the greatest degree of affectation have been identified, risk reduction strategies can be established in accordance with the most urgent needs of the territory. The research that has been developed is descriptive and the interaction of methodologies was carried out, which makes it qualitative-quantitative, with a non-experimental and transversal design. By working together with technicians, authorities and the inhabitants of the sector, it was possible to establish a sample of 21 families surveyed, for which the survey was used as the main technique, which was complemented with interviews, field trips and field practices; on the other hand, among the instruments that were of great help, observation cards, questionnaires and interview scripts were used. For the evaluation of physical, economic, environmental and social vulnerability, variables and indicators were adapted from the CENEPRED methodology and the emotional intelligence test, which was adapted to the conditions of the Tambán neighborhood, thus allowing for the identification of the areas with the greatest vulnerability, This allowed the identification of the areas with the greatest impact of vulnerability and subsequently established measures for recovery and risk reduction, which seek to strengthen the entire system of neighborhood organization focused on resilience, which promotes better living conditions and above all, that these are sustainable and sustainable.